-x+70=-86+5x

Simple and best practice solution for -x+70=-86+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+70=-86+5x equation:


Simplifying
-1x + 70 = -86 + 5x

Reorder the terms:
70 + -1x = -86 + 5x

Solving
70 + -1x = -86 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
70 + -1x + -5x = -86 + 5x + -5x

Combine like terms: -1x + -5x = -6x
70 + -6x = -86 + 5x + -5x

Combine like terms: 5x + -5x = 0
70 + -6x = -86 + 0
70 + -6x = -86

Add '-70' to each side of the equation.
70 + -70 + -6x = -86 + -70

Combine like terms: 70 + -70 = 0
0 + -6x = -86 + -70
-6x = -86 + -70

Combine like terms: -86 + -70 = -156
-6x = -156

Divide each side by '-6'.
x = 26

Simplifying
x = 26

See similar equations:

| 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) | | (4+4)(x+2)=(2+2) | | -5x=2x | | x^2-12x=8064 | | 8(5k-3)=-264 | | x^2-12x=5440 | | 9(y+5)=8y-6 | | 125*.38= | | -2x+2(-4x-3)=74 | | 4(y-8)=9+5y | | 28-6(2x+4)= | | 3(x+2)=4(x+2) | | 2x-1=63 | | z-(2+1i)z+(-1+7i)=0 | | 3(d-0.8)=4x+4 | | -34+3x=18+5x | | 19.3-4.507= | | 5x-31=2x+8 | | x+73=3x+9 | | 1-a^2=x^2-2ax+1 | | -6(2t+6)=-12 | | 3r=-18 | | x=7y-47 | | 0.14y+0.07(y+6000)=1260 | | 12-3(4x+2)=3x+4(x-8) | | 3[x+5(6-x)+24]-11=79-15x | | 3-y=6y+7 | | 4(-18+24)= | | 2x-70=50+6x | | (-6+12i)(-7-9i)=0 |

Equations solver categories